The “FitBrain” program: implementing exergaming & dual-task exercise programs in outpatient clinical settings - Glatt, Ryan M.; Patis, Corwin; Miller, Karen J.; Merrill, David A.; Stubbs, Brendon; Adcock, Manuela; Giannouli, Eleftheria; Siddarth, Prabha (Frontiers in Sports and Active Living, 2024)
Dual-task training and exergaming interventions are increasingly recognized for their potential to enhance cognitive, physical, and mood outcomes among older adults and individuals with neurological conditions. Despite this, clinical and community programs that use these interventions are limited in availability. This paper presents the “FitBrain” program, an outpatient clinical model that combines dual-task and exergaming interventions to promote cognitive and physical health. We review the scientific rationale supporting these methods, detail the structure and methodology of the FitBrain program, and provide examples of session designs that integrate dual-tasking through exergaming. The paper also addresses implementation considerations, such as tailoring interventions to specific populations, ensuring user-centered design, and leveraging accessible technologies. We discuss key challenges, including limited research on programs utilizing multiple technologies and cost constraints, and propose directions for future research to refine best practices and evaluate the comparative effectiveness of multimodal vs. singular interventions. This paper aims to inform clinicians and program developers on implementing dual-task and exergaming interventions within diverse clinical and community settings by offering a structured model and practical guidelines.